Internal and External Factors Associated with Preoperative Anxiety: A Cross-Sectional Study - Trisna Vitaliati; Lilis Setiyowati (LPPM Universitas dr. Soebandi, 2026)
Introduction: Anxiety is a common psychological response experienced by patients before undergoing surgery. This condition can affect physiological stability, the healing process, as well as the success of surgery. Factors that affect a patient's anxiety level can come from internal aspects such as age, gender, education level, and knowledge; as well as external factors such as family support, information from health workers, and previous surgery experience. This study aims to analyze internal and external factors related to the patient's anxiety level before surgery. Methods: This study uses an analytical descriptive design with a cross sectional approach. The population obtained was obtained from the average number of surgery patients each month of 100 people. The number of samples calculated using the slovin formula was obtained by 80 respondents who were taken using the Random Sampling technique. Data collection was carried out using the Hamilton Anxiety Rating Scale questionnaire to measure anxiety levels as well as questionnaires of related factors. Data analysis uses chi-square tests to look at the relationships between variables. Results: The results of the study showed that the factors related to the level of anxiety in pre-operative patients through statistical tests were age (pvalue = 0.04), education level (pvalue = 0.02), surgical experience (pvalue = 0.001) and family support (pvalue = 0.001). Meanwhile, another factor that was not related to the anxiety level of pre-operative patients was gender (pvalue = 0.216). Conclusions: Both internal and external factors have an influence on the patient's anxiety level before surgery. Efforts are needed to improve pre-operative education and psychological support for patients to reduce anxiety levels and increase readiness for surgery.